2022
DOI: 10.53043/2347-3894.acam90025
|View full text |Cite
|
Sign up to set email alerts
|

Short Review on srBERT: Automatic Article Classification Model for Systematic Review Using BERT

Abstract: Systematic reviews (SRs) have been recognized as the most rigorous and reliable approach to enable evidence-based medicine. However, the considerable workload required to create SRs prevents reflecting the latest knowledge. This study automated the classification of included articles by adopting the Bidirectional Encoder Representations from Transformers (BERT) algorithm. By pretraining with abstracts of articles and a generated vocabulary fine-tuned with titles of articles, the proposed srBERTmy overcomes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The transformer architecture is an encoder-decoder model training structure that does not use recurrence and convolutions [17]. Prior work showed that using PLMs can significantly increase effectiveness in ad-hoc search [18] as well as in professional search [19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The transformer architecture is an encoder-decoder model training structure that does not use recurrence and convolutions [17]. Prior work showed that using PLMs can significantly increase effectiveness in ad-hoc search [18] as well as in professional search [19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%